SEBARAN BENTIK FORAMINIFERA PADA SEDIMEN PERMUKAAN DI PERAIRAN PANTAI SERGANG DAN MAROK TUA KABUPATEN LINGGA - Aslinda, Sri; Amin, Bintal; ', Rifardi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in June 2015. The sampling and measurement of water quality were carried out in Sergang and Marok Tua coastal waters of Singkep Island, Riau Archipelago. This study was aimed to determine the distribution of benthic foraminifera and relative sedimentation rate in both areas. Survey method was used by taking samples from 2 stasions with 3 replicates at each stasion. Samples of sediments were taken and then analyzed to determine the number of individual, species, distribution pattern, the relative sedimentation rate and sediment fractions. The results showed that the number of individual of benthic foraminifera found in the wartes of Sergang were higher than in Marok Tua. In contrary the number of species of benthic foraminifera found in Marok Tua were higher than in Sergang. Sediment fraction in Sergang was dominated by fine sand and very fine sand. Based on Morisita index, the pattern of benthic foraminifera distribution was categorized as cluster. Results of the relative sedimentation rate calculation were divided into high in Sergang coastal waters that has limited antrophogenic activities with an average of 83.06 %. Lower sedimentation rate was found in Marok Tua with an average of 67.47%. Marok Tua coastal waters has more antrophogenic activities such as fishing boat activities, residential as well as tin and sand mining areas.Keywords : benthic foraminifera, sedimentation, mining, antrophogenic